Albuminuria predicts kidney events in IgA nephropathy - Faucon, Anne-Laure; Lundberg, Sigrid; Lando, Stefania; Wijkström, Julia; Segelmark, Mårten; Evans, Marie; Carrero, Juan-Jesús (Nephrology, dialysis, transplantation, 2025)
KDIGO recommends proteinuria <1 g/d as a treatment target in patients with immunoglobulin A nephropathy (IgAN) because of high risk of progression to kidney failure. However, long-term kidney outcomes in patients with low-grade proteinuria remain insufficiently studied. We enrolled patients with biopsy-proven primary IgAN from the Swedish Renal Registry and analyzed associations between urine albumin-to-creatinine ratio (uACR, in categories <0.3, 0.3-0.5, 0.5-1.0, 1.0-1.5, 1.5-2.0, and ≥2.0 g/g) and the occurrence of major adverse kidney events [MAKE, a composite of kidney replacement therapy (KRT) and >30% decline in estimated glomerular filtration rate (eGFR)]. We also explored the risk of kidney events associated with change in uACR within a year. We included 1269 IgAN patients (74% men, median 53 years, mean eGFR 33 ml/min/1.73 m², median uACR 0.7 g/g). Over a median follow-up of 5.5 [2.8; 9.2] years, 667 MAKE and 517 KRT events occurred, and 528 patients experienced >30% eGFR decline. Compared with uACR < 0.3 g/g, any higher uACR category was strongly and incrementally associated with the risk of MAKE [adjusted hazard ratios (HR) ranging from 1.56 (95%CI 1.14-2.14) if uACR 0.3-0.5 g/g to 4.53 (3.36-6.11) if uACR ≥ 2.0 g/g], KRT (HR ranging from 1.39 to 4.65), and eGFR decline >30% (HR ranging from 1.76 to 3.47). In 785 patients who had repeated uACR measurements within a year, and compared with stable uACR, the risk of kidney events was lower if uACR decreased by 2-fold (HR ranging from 0.47 to 0.49), and higher if uACR increased by 2-fold (HR from 1.18 to 2.56), irrespective of baseline uACR. There is substantial risk of adverse kidney outcomes among patients with IgAN and uACR between 0.3 and 1.0 g/g, a population currently considered at low risk of CKD progression. Reduction in uACR is associated with better kidney outcomes, irrespective of baseline uACR.